Role of Diffusion MRI and Apparent Diffusion Coefficient Measurement in the Diagnosis, Staging and Pathological Classification of Bladder Tumors - Daggulli, Mansur; Onur, Mehmet Ruhi; Firdolas, Fatih; Onur, Rahmi; Kocakoc, Ercan; Orhan, Irfan (Karger, 2011)
Objectives: Our aim was to investigate the role of simultaneous apparent diffusion coefficient (ADC) measurement and diffusion-weighted MRI (DWMRI) in the diagnosis and differentiation of bladder masses. Methods: We examined 45 patients presenting with hematuria by dynamic and diffusion MRI (at b100, b600, b1000 gradients) and cystoscopy. Thirty healthy volunteers without hematuria were also included in the study. Results from imaging techniques were compared to cystoscopic and histopathologic findings. The ADC values of benign and malignant bladder masses, and bladder tissue in healthy subjects were measured and compared with each other. Results: The mean ADC values of benign (n = 10) and malignant lesions (n = 35) were significantly lower than the mean ADC values of adjacent bladder walls and bladder walls of healthy subjects at all 3 gradients (p < 0.05). However, no significant difference was detected between benign and malignant lesions (p > 0.05). Mean ADC values of invasive tumors were significantly lower than superficial malignancies at b600 and b1000 gradients. The mean ADC values of transitional cell tumors were significantly higher than squamous cell tumors at b100 and b600 gradients. Conclusion: Simultaneous measurement of ADC and DWMRI provided useful information in the diagnosis, staging and histopathological classification of bladder tumors. Copyright (C) 2011 S. Karger AG, Basel
Keywords: MRI; Diffusion-weighted MRI; Bladder cancer; Apparent diffusion coefficient value; Hematuria